"Doc McStuffins: Doctor for a Day" Virtual Reality (DocVR) for Pediatric Preoperative Anxiety and Satisfaction: Pediatric Medical Technology Feasibility Study - Gold, Jeffrey I; Annick, Erin T; Lane, Arianna S; Ho, Katherine; Marty, Ryan T; Espinoza, Juan C (JMIR Publications, 2021)
BackgroundPreoperative anxiety is a common occurrence among children and is associated with a host of maladaptive postoperative behaviors. Consequently, increased attention has been placed on interventions to reduce preoperative anxiety and its associated outcomes. Child Life preparation prior to surgery includes evidence-based practices such as age-appropriate distraction and therapeutic play. Virtual reality (VR) is a promising addition to the Child Life toolbox to address anxiety prior to surgery. The current study evaluates the implementation and feasibility of a VR experience, "Doc McStuffins: Doctor for a Day Virtual Reality Experience" (DocVR), developed by Disney Junior in collaboration with Children's Hospital Los Angeles, to target pediatric preoperative anxiety. ObjectiveThe primary aim of this study was to examine the feasibility and efficacy of DocVR for preoperative anxiety. A secondary aim was to improve patient, caregiver, and health care provider satisfaction with the preoperative experience. MethodsIn this study, 51 patients (age 6-14 years) scheduled for surgery in the ambulatory surgery center and the main operating room at Children's Hospital Los Angeles were approached to participate in Disney's DocVR experience. The patients played the DocVR experience for an average of 18 minutes (3-55 minutes). Irrespective of surgical procedure, patients and their families were eligible, as long as they had no known marked cognitive or visual impairments that would interfere with completing the survey and engaging in the DocVR experience. ResultsPatients who tried the DocVR experience (n=51) responded overwhelmingly positively to both the VR technology and to the game itself. Patients experienced a statistically significant decrease in anxiety following DocVR game play (Z=-3.26, P=.001). On the Facial Affective Scale, the percentage of patients who chose the face with the most positive facial expression to represent their affect increased from 23% (12/51) pre-VR to 49% (25/47) post-VR. Furthermore, 97% (38/39) of patients reported feeling more comfortable at the hospital, and 74% (28/38) reported feeling less scared at the hospital after playing the game. The game was enjoyed by 94% (46/49) of patients, and 88% (30/34) of patients reported feeling both "Interested" and "Involved" in the game. ConclusionsDocVR is a feasible and beneficial VR experience to relieve pediatric preoperative anxiety and improve satisfaction in the preoperative area. The VR experience resulted in a decrease in overall anxiety and an increase in overall positive affect during the preoperative time. Patients also responded positively to the game, confirming their interest in the content and affirming the quality of the DocVR experience. The positive response to the game indicates that DocVR has the potential to make the overall preoperative experience less anxiety-producing and more comfortable, which leads to improved patient satisfaction. Naturally, improved patient outcomes lead to improved caregiver and health care provider satisfaction.